2017
DOI: 10.1111/ijfs.13418
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of phytochemicals, enzymatic and antioxidant activities in germinated mung bean (Vigna radiata L. Wilezek)

Abstract: Summary Vitamin C, phenolic and flavonoid contents along with enzymatic and antioxidant activities were determined in germinated mung bean (Vigna radiate). Elevated levels of vitamin C 72.31 ± 0.62 mg/100 g FW and flavonoid content 85.57 ± 0.59 mg CE/100 g FW were estimated for euphylla after 6 days of germination. Moreover, maximum peroxyl radical scavenging activity 645.4 ± 28.5 μmol ASA equiv./100 g FW was also determined in euphylla. However, seed coat has the highest content of phenolic content (568.4 ± 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The phenolic content of extracts was determined using the Folin-Ciocalteu method (Guo et al, 2012;Wang et al, 2017c). Gallic acid was used as standard in this assay.…”
Section: Determination Of Phenolics and Flavonoidsmentioning
confidence: 99%
“…The phenolic content of extracts was determined using the Folin-Ciocalteu method (Guo et al, 2012;Wang et al, 2017c). Gallic acid was used as standard in this assay.…”
Section: Determination Of Phenolics and Flavonoidsmentioning
confidence: 99%
“…Sprouted soybean is a traditional and popular soybean product in Orient. Significant changes of the biochemical, nutritional and sensory characteristics have occurred in cereals during germination (Sharma et al, 2016;Wang et al, 2017). It is reported that the content of c-aminobutyric acid (GABA) increases significantly during germination in soybean, suggesting that germinated soybean could be a good source of GABA (Quinhone & Ida, 2015;Wang et al, 2015a;Huang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The vitamin C content of wheat plantlet juice was determined using the 2,6-dichloroindophenol (DIP) titrimetric method as reported previously (Wang et al 2017 ) with some modification. Briefly, 1.0 mL wheat plantlet juice and 9.0 mL chilled 2% (w/v) metaphosphoric acid buffer were added to a 50 mL conical flask for titration.…”
Section: Methodsmentioning
confidence: 99%